CREATING GRADES AND STANDARD LEVELS ACCORDING TO SPECIALIZED SKILL TESTS DESIGNED FOR THE 50M BACKSTROKE SWIMMING CATEGORY OF APPLICANTS - Asst. Lect Wissam Halil Manati; Prof. Dr. Ali Farhan Hussein; Assist. Prof. Dr. Makki Jabbar Odeh (Scholars Digest Publishing, 2024)
The importance of the research lies in finding standard grades and levels according to specialized skill tests to know the strengths and weaknesses of the performance levels in the 50m backstroke for the applicant category. Therefore, the importance of the research was evident in the evaluation process using tests and measurement for the specialized tests designed (skills) that reflect the condition of the real swimmer. The research problem that the researchers, who through this research wanted to find solutions to this problem, were born out of the fact that the process of evaluation and finding standards is a matter of quick decisions and is a personal evaluation based on scientific foundations. The researchers used the descriptive survey method to achieve the research objectives. The research sample included swimmers from clubs (Baghdad-Maysan) for the 2023/2024 sports season. The SPSS Ver 21 statistical package was used. A set of conclusions were reached, the most important of which are: 1- Specialized skill tests are the best way to determine the true condition of swimmers. 2- The levels found by the researchers represent the true level of swimmers’ skill capabilities and capabilities. 3- Most of the swimmers among the research sample were at the average level, at which the highest percentages were achieved. The most important recommendations are: 1- Adopting the specialized tests and levels created by researchers. 2- Innovation in creating standard grades and levels contributes to identifying the strengths and weaknesses of swimmers.
Keywords: Standard levels - skill tests - swimming (50) meters.